2020
DOI: 10.1002/jaba.797
|View full text |Cite
|
Sign up to set email alerts
|

Replicating stimulus‐presentation orders in discrimination training

Abstract: Children with autism spectrum disorder (ASD) are taught conditional discriminations often during early intervention. Auditory-visual conditional discrimination (AVCD) training requires the presentation of multiple antecedent stimuli, and the order of stimulus presentation varies in the literature. This series of studies replicated previous literature on stimulus-presentation order in AVCD training. In Experiment 1, we compared sample-first and comparisons-first arrangements in 8 comparisons with 4 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These findings are consistent with Bergmann et al. (2020) which suggested that the advantages of different stimulus‐presentation orders may differ given the specific characteristics (e.g., echoic repertoires) of the participants. Future researchers could further examine the role of covert echoics in this context.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with Bergmann et al. (2020) which suggested that the advantages of different stimulus‐presentation orders may differ given the specific characteristics (e.g., echoic repertoires) of the participants. Future researchers could further examine the role of covert echoics in this context.…”
Section: Discussionsupporting
confidence: 91%
“…(2019) required a trial‐initiation response (i.e., participants touched a paper and tacted the correct color of the paper prior to the start of the session), and Bergmann et al. (2020) used nondifferential reinforcement and made modifications to the procedures (e.g., DOR, descriptive praise, instructive feedback) based on participants' responding. Additionally, only one of the three participants in Cubicciotti et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimenter presented a three-stimulus horizontal array placed approximately 15 cm in front of the participant on the table. The experimenter ensured attending to the array, presented the auditory sample stimulus, and repeated it every 2 s (e.g., "cup," "cup," "cup" with 2 s between presentations; Bergmann et al, 2021). Due to the timing of the sample re-presentation, participants had 6 s to engage in a response.…”
Section: Identification Of Stimuli and Baselinementioning
confidence: 99%
“…The child was given 5 s to respond. The auditory sample was programmed to repeat after 2 s (Bergmann et al 2020;Cubicciotti et al, 2018).…”
Section: Auditory-visual Conditional Discriminations (Miles and Silas)mentioning
confidence: 99%